ASME 2013 7th International Conference on Energy Sustainability 2013
DOI: 10.1115/es2013-18336
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Manifold Area Change in a Flat Solar Collector

Abstract: A numerical analysis of the characterization of the water flow through a flat solar collector is presented. The manifold area change for minimizing the water flow variation in the solar collector is analyzed. The area ratio in the inlet and outlet of the manifolds were modified in a range of Am/Ao = 1 to 4, where Am and Ao are the cross-sectional area modified and original of the manifolds, respectively. The solar collector investigated is equipped with six riser tubes, which are attached to the manifolds pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A variable area analysis for a flat plate solar collector was performed by Uzarraga-Rodriguez et al [44]. The results showed that an increase on the ratio of the inlet and outlet area of the solar collector contributes on obtaining a uniform distribution through the riser tubes, slightly decreasing the pressure drop.…”
Section: Strategies To Reduce the Flow Non-uniformitymentioning
confidence: 99%
“…A variable area analysis for a flat plate solar collector was performed by Uzarraga-Rodriguez et al [44]. The results showed that an increase on the ratio of the inlet and outlet area of the solar collector contributes on obtaining a uniform distribution through the riser tubes, slightly decreasing the pressure drop.…”
Section: Strategies To Reduce the Flow Non-uniformitymentioning
confidence: 99%